An Analysis of The Impact of Work from Home and Flexible Arrangements on The Welfare of Banking Sector Employees - Merson Simbolon; Ishak Ishak; Fauziah F. Farawowan; Mustofa As’ady; Fitri Devi Lestari Izaak (Journal Of Human And Education (JAHE), 2026)
The digital transformation and the adoption of post-pandemic work patterns have fundamentally altered the operational landscape of the banking sector through the implementation of Work From Home (WFH) and Flexible Work Arrangements (FWA). This study aims to analyze the comprehensive impact of WFH and FWA implementation on employee welfare in the banking industry, encompassing psychological, physical, social, and work-life balance dimensions. Utilizing a mixed-methods approach that integrates quantitative surveys of banking personnel with in-depth qualitative interviews, this research evaluates how spatial and temporal flexibility influence stress levels, job satisfaction, and employee productivity (Allen et al., 2020; Bloom et al., 2022). The findings indicate that while FWA offers significant autonomy and mitigates commuting stress, it also introduces novel challenges such as technostress, the blurring of boundaries between professional and personal life (work-family conflict), and prolonged digital workloads (Tarafdar et al., 2019; Wang et al., 2021). As a result, this study concludes that the efficacy of FWA in enhancing banking employee welfare relies heavily on adaptive leadership, clear digital boundaries, and responsive organizational support systems. The practical implications of this study provide strategic guidance for banking management in formulating sustainable flexible work policies that safeguard employee mental health while maintaining operational performance (Bakker & Demerouti, 2017).